2018
DOI: 10.1002/celc.201801291
|View full text |Cite
|
Sign up to set email alerts
|

Probing the 3‐step Lithium Storage Mechanism in CH3NH3PbBr3 Perovskite Electrode by Operando‐XRD Analysis

Abstract: Organic‐inorganic hybrid materials have gradually become one of the most actively studied research fields due to their fascinating properties. The reaction between lithium and organic‐inorganic halide perovskite has just recently been proposed. However, the exact mechanisms taking place in this electrode material have not been fully elucidated, yet. To shed light on these processes an operando‐X‐ray diffraction study has been performed and is reported herein. According to our results the lithiation of CH3NH3Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Eventually, the Li-Pb alloy forms, which cannot be converted back to the initial states. [179] Figure 6. Lithium incorporation in halide perovskites is accompanied by both conversion and intercalation processes (left), with the conversion process suggested to dominate during lithium uptake.…”
Section: (8 Of 20)mentioning
confidence: 99%
“…Eventually, the Li-Pb alloy forms, which cannot be converted back to the initial states. [179] Figure 6. Lithium incorporation in halide perovskites is accompanied by both conversion and intercalation processes (left), with the conversion process suggested to dominate during lithium uptake.…”
Section: (8 Of 20)mentioning
confidence: 99%
“…Molecular or polymeric selective layers hardly prevent this interdiffusion. [28][29][30][31][32] In addition to that, dopants such as LiTFSI and tert-butyl pyridine can diffuse and react with the perovskite and layers, [33][34][35] further degrading the device performances. A uniform NiO layer ideally insulates the perovskite lm from the electrode, thus preserving the structural integrity of the device.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that batteries using CH3NH3PbBr3, which is 3D-HHP, show the discharge plateau at ~2.3 V vs. Li, corresponding to ~1.7 V vs. Li-In alloy, through the formation of the Li + -inserted CH3NH3PbBr3. 25 In case of the all-solid-state battery prepared with 2D-HHP, a similar discharge plateau was observed at ~1.5 V vs. Li-In alloy. In contrast, this discharge plateau was not observed in a lithium-ion battery using PbO, where only conversion and alloying−dealloying process has been reported.…”
mentioning
confidence: 52%
“…16−18 Their potential as electrode materials has been recently explored, 19−24 and the lithium storage mechanism by insertion/extraction, conversion, and alloying−dealloying has been proposed. 25 Their characteristic structure allows an efficient ionic diffusion (Li + , Na + ). Actually, the coefficient of Li + diffusion is as high as ~10 −7 cm 2 s −1 , implying that Li + conductivity of lithiated HHP can reach ~10 −3 S cm −1 .…”
mentioning
confidence: 99%